Neurophysiological Effects Associated With Subliminal Conditioning of Appetite Motivations - Amd, Micah; Baillet, Sylvain (Frontiers in Psychology, 2019)
When attempting to encourage eating, explicitly providing statements like ‘eating is pleasant’ may produce little effect. This may be due to subjective, negatively-valenced narratives evoked by perception of the verb ‘eating' (e.g., eating  fat  lonely), overriding any explicitly provided eating-pleasant valence information. In our study, we presented eating-related verbs under subliminal visual conditions to mitigate the onset of eating-associated deliberation. Verbs were linked with neutral or positively valenced terms across independent blocks. Modulations of event-related magnetoencephalographic (MEG) components and parietal activations in the alpha range (8-12 Hz) illustrated a significant effect of valence during pre-lexical time windows. We found significantly greater saliva production and declarations of increasing hunger after eating-related verbs were linked with positive terms. Orally reported preferences did not vary between conditions.